Crystal engineering in confined spaces. A novel method to grow crystalline metal phosphonates in alginate gel systems - Stavgianoudaki, Nikoleta; Papathanasiou, Konstantinos E.; Pérez-Colodrero, Rosario Mercedes; Choquesillo-Lazarte, Duane; García-Ruíz, Juan M.; Cabeza-Díaz, Aurelio; García-Aranda, Miguel Ángel; Demadis, Konstantinos D. (The Royal Society of Chemistry, 2012)
In this paper we report a crystal growth method for metal phosphonate frameworks in alginate gels. It consists of a metalcontaining alginate gel, in which a solution of phosphonate ligand is slowly diffused. Crystals of metal phosphonate products are formed inside the gel. We have applied this for a variety of metal ions (alkaline-earth metals, transition metals and lanthanides) and a number of polyphosphonic acid and mixed carboxy/phosphonic acid ligands.
Keywords: Química; Cristalografía; X-ray diffraction; Metal phosphonates; Alginate gel systems